Isolation, Hemisynthesis And Characterisation Of Pentacyclic Triterpenoids From Diospyros Foxworthyi Bakh. (Ebenaceae) And Their Biological Activities - Abd Ghani, Muhammad Solehin (2024)
Diospyros foxworthyi is a tropical plant species of Ebenaceae family that is native to Malaysia. This genus is rich with pentacyclic triterpenoids in the form of lupane-based skeleton. The preliminary study of this genus showed good inhibition of dengue protease, which subsequently intrigue to further its phytochemical findings. The present study aimed to investigate the chemical composition of D. foxworthyi, synthesis of the triterpenoids derivatives and evaluate their biological activities.